Peranan Badan Mubaligh Kristian dalam Perkembangan Pendidikan Formal Wanita di Sarawak, 1848–1930: The Role of Christian Missionaries in the Development of Women’s Formal Education in Sarawak, 1848–1930 (KEMANUSIAAN The Asian Journal of Humanities, 2025)
In Sarawak, the Christian missionaries carried out their Christianisation by establishing missionary schools. Through the establishment of the missionary school, they not only want to Christianise the Dayak and Chinese communities but also the Malay community. James Brooke was seen supporting the effort because he did not prohibit the missionaries’ actions. However, the effort was not continued after Francis Thomas McDougall retired in 1866. Despite failing to Christianise the Malay community, the missionaries succeeded in introducing a formal education system for women in Sarawak through the establishment of missionary girls’ schools. Therefore, this study was conducted to discussing the role of Christian missionaries in the development of formal education for women in Sarawak. With that, qualitative research has been carried out by analysing the selected sources especially the Sarawak Gazette. Through this study, it can be seen that the Christian missionaries played an important role in the development of women’s education because the establishment of girl’s schools has given women in Sarawak the opportunity to go to school. Its’ also succeeded in changing the public’s perception of intelligent women. Following that, the community began to allow their daughters to go to school. In fact, the Sarawak people’s itself also setting up their own girl’s school. This shows that the Christian missionary were the pioneers of formal education for women in Sarawak.Badan mubaligh Kristian di Sarawak menjalankan dakwah Kristianisasi dengan mendirikan sekolah mubaligh. Melalui penubuhan sekolah tersebut, mereka bukan sahaja ingin mengkristiankan masyarakat Dayak dan Cina tetapi juga masyarakat Melayu. James Brooke dilihat menyokong usaha tersebut kerana beliau tidak melarang perbuatan para mubaligh berkenaan. Namun demikian, usaha itu tidak diteruskan selepas Francis Thomas McDougall bersara pada tahun 1866. Meskipun gagal mengkristiankan masyarakat Melayu, pihak mubaligh berjaya memperkenalkan sistem pendidikan formal untuk kaum wanita di Sarawak menerusi penubuhan sekolah perempuan mubaligh. Justeru, kajian ini dilakukan untuk membincangkan peranan badan mubaligh Kristian dalam perkembangan pendidikan formal untuk wanita di Sarawak. Penyelidikan kualitatif telah dilakukan dengan menganalisis sumber-sumber yang terpilih. Sumber yang banyak digunakan adalah Sarawak Gazette. Menerusi kajian ini, badan mubaligh Kristian didapati memainkan peranan penting dalam perkembangan pendidikan wanita di Sarawak kerana penubuhan sekolah perempuan oleh badan mubaligh memberi peluang kepada kaum wanita untuk bersekolah. Selain itu, penubuhan sekolah perempuan mubaligh juga berjaya mengubah tanggapan masyarakat terhadap wanita pandai. Susulan itu, masyarakat mula membenarkan anak perempuan mereka bersekolah seperti anak lelaki. Masyarakat Sarawak juga mengikut jejak langkah badan mubaligh dengan mendirikan sekolah perempuan mereka sendiri. Keadaan ini menunjukkan bahawa badan mubaligh Kristian merupakan perintis kepada perkembangan pendidikan formal untuk kaum wanita di Sarawak.